1982
DOI: 10.1210/jcem-54-1-172
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Regulation of Parathyroid Hormone Release by Calcium in Secondary Hyperparathyroidism due to Chronic Renal Failure*

Abstract: Dispersed parathyroid cells were employed to study calcium-regulated parathyroid hormone (PTH) release in severe secondary hyperparathyroidism due to chronic renal insufficiency. Cell preparations were obtained from 16 parathyroid glands of 6 patients undergoing subtotal parathyroidectomy for parathyroid bone disease and/or hypercalcemia. The effects of increasing ambient calcium concentration on immunoreactive PTH release in vitro were assessed and compared with results observed in cells prepared from 7 adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
80
2
6

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(95 citation statements)
references
References 26 publications
7
80
2
6
Order By: Relevance
“…Thus, the correlation between Cab and the set point decreased at 5-6 weeks of 2 HPT. The increase in the set point found at 5-6 weeks, when compared with 2-3 weeks, is in agreement with previous reports that have identified a tendency to an increased set point of the PTH-Ca 2+ curve in the course of primary (Brown et al 1979) and secondary (Brown et al 1982, Malberti et al 1993, Goodman et al 1998 hyperparathyroidism. However, in these studies the progression of hyperparathyroidism was accompanied by an increase in extracellular Ca 2+ while in our study plasma Ca 2+ remained low.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the correlation between Cab and the set point decreased at 5-6 weeks of 2 HPT. The increase in the set point found at 5-6 weeks, when compared with 2-3 weeks, is in agreement with previous reports that have identified a tendency to an increased set point of the PTH-Ca 2+ curve in the course of primary (Brown et al 1979) and secondary (Brown et al 1982, Malberti et al 1993, Goodman et al 1998 hyperparathyroidism. However, in these studies the progression of hyperparathyroidism was accompanied by an increase in extracellular Ca 2+ while in our study plasma Ca 2+ remained low.…”
Section: Discussionsupporting
confidence: 92%
“…In vitro experiments using parathyroid glands excised from azotemic patients with severe 2 HPT have shown an increase in the set point, which may represent an intrinsic abnormality of PTH secretion (Brown et al 1982). However, clinical studies with hemodialysis patients have provided a variety of results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results remain controversial among the reported studies, and the effect of these SNPs in the VDR gene on ESRD risk in the Chinese population remains unclear (Fernández et al, 1997;Wang et al, 2004;El-Shehaby et al, 2013). Furthermore, vitamin D and its receptor have important roles in determining calcium-regulated parathyroid hormone (PTH) secretion (Brown et al, 1982). Few studies have reported the association of genetic variants of the VDR gene with the development of renal osteodystrophy (RO) in patients with ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…It presumably involves dysfunction of the mechanism by which the parathyroid cells sense changes in plasma calcium (4). PG from patients with severe secondary or tertiary hyperparathyroidism (HPT) have an elevated set-point for Ca ϩϩ in vitro (5). A substantial reduction in the expression of the Ca ϩϩ -sensing receptor (CaR) protein and mRNA has been demonstrated in hyperplastic parathyroid glands from uremic patients (6,7).…”
mentioning
confidence: 99%